Between Symbolic Inclusion and Structural Exclusion: A Critical Analysis of Governance, Capability Deprivation, and the Marginalization of Visually Impaired Artists and Sportspersons in Khyber Pakhtunkhwa, Pakistan - Rahman Said; Dr. Shakeel Ahmed (`, 2026)
Despite growing international and national commitments toward disability inclusion, visually impaired persons in Pakistan particularly those engaged in arts and sports continue to experience profound structural exclusion. This study critically examines the challenges faced by visually impaired artists and sportspersons in accessing inclusive opportunities in Khyber Pakhtunkhwa (KP), with a specific focus on governance failures, institutional practices, and capability deprivation. Drawing on qualitative data generated through in-depth interviews with visually impaired individuals, trainers, and institutional stakeholders, the study reveals that disability-inclusive policies in Pakistan largely remain symbolic in nature. Weak implementation mechanisms, fragmented institutional coordination, inaccessible infrastructures, and persistent charity-based approaches undermine the conversion of individual talent into recognized social and professional opportunities. Using the Capability Approach and the Social Model of Disability as theoretical lenses, the paper argues that exclusion is not primarily rooted in impairment but in systemic deprivation of enabling conditions. The findings further highlight intersectional dimensions of exclusion, particularly along gender and regional lines. The study contributes to social work and social policy scholarship by exposing the disjuncture between policy commitments and lived realities and by calling for a shift from symbolic inclusion toward rights-based, capability-enhancing governance frameworks for visually impaired persons in Pakistan. Keywords: Visual impairment; disability inclusion; capability approach; governance; arts and sports; social policy; Khyber Pakhtunkhwa; Pakistan https://doi.org/10.5281/zenodo.18343058